Influence of scapular dyskinesis, kinesiotaping and fatigue on tennis serve performance - Tooth, C.; Schwartz, C.; Fransolet, C.; Tubez, F.; Colman, D.; Croisier, J. L.; Forthomme, B. (International Journal of Performance Analysis in Sport, 2020)
The objective of this study was to assess the influence of scapular kinesiotaping and scapular muscle fatigue on tennis performance in dyskinetic players, with regard to racket velocity and the accuracy of the serve. Fifteen tennis players with scapular dyskinesis on the dominant side were assessed when performing 15 serves in three different conditions: standard condition, with kinesiotaping and with scapular fatigue. Racket velocity was estimated using a three-dimensional optoelectronic system. Accuracy was measured using a 1 m2 scoring system. Considering all population, kinesiotaping did not significantly increased racket velocity but in decreased until 45% the accuracy of the serve. As to scapular muscle fatigue, it significantly decreased both racket velocity (4%) and accuracy of the serve (until 55%) in all the sample. So, scapular kinesiotaping would not be recommended to increase performance in dyskinetic tennis players, especially if they are not used to. Scapular muscle fatigue, by disrupting kinetic chain transfer, lead to a decrease in tennis serve performance. In view of the important numbers of serves during a tennis match, improving specific endurance of scapular stabilisers muscles would have an interest in this population to maintain performance during a match.